Wawasan Al-Qur’an Tentang Ukhuwa - Nurchalis Aziz; Hasyim Haddade; Hamka Ilyas (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
Ukhuwa, or brotherhood, is a fundamental value in Islamic teachings, extensively discussed both explicitly and implicitly in the Quran. This study aims to uncover and deeply examine the Quranic insights into the concept of ukhuwa, including its terminology, forms, and implications for the social life of Muslims. The approach used in this study is qualitative, using the thematic interpretation method (maudhu'i), which explores verses related to brotherhood, including ukhuwa Islamiyah (Islamic brotherhood), ukhuwa insaniyah (human brotherhood), and ukhuwa wathaniyah (national brotherhood). The results of this study indicate that the Quran emphasizes the importance of building harmonious relationships, helping each other in good deeds, forgiving one another, and maintaining unity amidst differences. The values of ukhuwa in the Quran are not only directed at fellow Muslims but also at all humanity as a manifestation of the universal grace of Islam. This research confirms that ukhuwa is the primary foundation for building a just, peaceful, and civilized society.